Theoretical analysis of a novel PCHE with enhanced rib structures for high-power supercritical CO2 Brayton cycle system based on solar energy. (1st May 2023) - Han, Zengxiao; Guo, Jiangfeng; Huai, Xiulan
Abstract: A printed circuit heat exchanger (PCHE) is one of the most significant components in the supercritical CO2 (SCO2 ) Brayton cycle system based on concentrated solar power, whose performance significantly affects the efficiency and compactness of the system. To improve the performance of PCHE with semicircular-straight channels, rib structures placed on the top flat wall of the semicircular channel are proposed, which are achieved by the double sides etched heat transfer plates, and the effects of the distributions of rib structures on the performance of channels are also investigated. The thermal-hydraulic performance of the conventional semicircular channel and the semicircular channel with different rib structures are compared. The results indicate that rib structures lead to an apparent increase of turbulence kinetic energy in channels, and improve the synergy between velocity and temperature gradient fields, leading to the heat transfer enhancement. Among the channels with different rib structures, the comprehensive performance of the semicircular channel with the spacing distribution of short rib structures (channel DR3) is the best, which is relatively 19.3–19.8% higher than that of the conventional semicircular channel. When the channel DR3 is adopted in PCHE, the effectiveness of PCHE could reach 98.4–98.7%, the efficiency of the SCO2 Brayton cycle system based on solar power could be increased by 15.3%, and the compactness of the system could be improved by 3.8%. This present work is of great significance for deepening the understanding of PCHE heat transfer mechanism and performance optimisation, as well as improving the overall performance and compactness of large-scale SCO2 -based power systems. Highlights: PCHE with rib structures was proposed for SCO2 -BC system based on solar power tower. PCHE with the spacing distribution of rib structures has the best thermal-hydraulic performance. Spacing distribution of rib structures improves thermal-hydraulic performance by 19.3–19.8%. Spacing distribution of rib structures improves efficiency and compactness of SCO2 -BC system by 15.3% and 3.8%.